A staff training course to build a radiocommunication worker disaster or emergency network - Amasiri, Watchara (Journal of Multidisciplinary Academic Research and Development (JMARD), 2021)
Based on collaboration from 14 October 2016 to 1 December 2017 between Thammasat University, the Office of The National Broadcasting and Telecommunications Commission (NBTC) and amateur radio organizations to establish a temporary amateur radio station at Thammasat University, Tha Prachan during the royal cremation ceremony for His Majesty King Bhumibol Adulyadej, this research anticipates the role of radio amateurs to support government agency communication operations in providing technical advice, equipment measuring support, and establishing and improving communication station efficiency. Training courses were developed to heighten the potential of radio amateurs and prepare them to assist government and private agencies with telecommunications in case of disaster or emergency.